2013
DOI: 10.1007/s00405-013-2682-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors confusing the diagnosis of laryngopharyngeal reflux: the role of allergic rhinitis and inter-rater variability of laryngeal findings

Abstract: The objective of the study was to determine the inter-rater variability in assessment of laryngeal findings and whether diagnosing laryngopharyngeal reflux based on the laryngeal findings and history alone without considering allergic rhinitis leads to the overdiagnosis and overtreatment of laryngopharyngeal reflux. Patients with positive and negative skin prick tests were recruited from an allergy clinic in a tertiary teaching university hospital. All subjects completed the Reflux Symptom Index (RSI) and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 14 publications
1
59
0
Order By: Relevance
“…Some authors think that the studies made until now did not confirm that LPR is so much present among dysphonic patients (26)(27)(28), and there is a significant overlap in the symptomatic presentation of patients with LPR and allergic laryngitis (15,28). The LPR and AR are difficult to be differentiated because they have similar signs and symptoms as reported.…”
Section: Discussionmentioning
confidence: 79%
“…Some authors think that the studies made until now did not confirm that LPR is so much present among dysphonic patients (26)(27)(28), and there is a significant overlap in the symptomatic presentation of patients with LPR and allergic laryngitis (15,28). The LPR and AR are difficult to be differentiated because they have similar signs and symptoms as reported.…”
Section: Discussionmentioning
confidence: 79%
“…Specificity and reliability of the RFS and laryngeal LPR findings in general, have been scrutinized and challenged by several studies. 3339 In its initial validation, the RFS was found to have an inter-rater correlation coefficient (ICC) of 0.90; indicating near perfect agreement among laryngologist-raters. 32 Since, documented inter-rater agreement has been less impressive, ranging from poor to fair.…”
Section: Consistencymentioning
confidence: 99%
“…32 Since, documented inter-rater agreement has been less impressive, ranging from poor to fair. 33, 35, 37, 39, 40 In one study, for example, only 35% of those with abnormal RFS had pathological reflux on pH studies, suggesting that true identification of LPR is occurring about 1/3 of time in clinical settings that primarily rely on physical findings to diagnose LPR in symptomatic patients. 38 Other authors reported discordance between RFS and pH results in 53% of participants referred for LPR evaluation.…”
Section: Consistencymentioning
confidence: 99%
See 1 more Smart Citation
“…There is also an emerging body of evidence that suggests environmental allergies may cause laryngeal symptoms, however, the symptom overlap and comorbidity between allergy and LTH has yet to be fully elucidated [4, 5]. The purpose of this study was to determine what factors are associated with LTH in a population of Canadian adults.…”
Section: Introductionmentioning
confidence: 99%